2018
DOI: 10.1080/00221325.2018.1454883
|View full text |Cite
|
Sign up to set email alerts
|

A Multimethodological Study of Preschoolers' Preferences for Aggressive Television and Video Games

Abstract: The association between aggressive media and related behavior is complicated, and the role of underlying genetics has not been adequately explored. A better understanding of the role of genetics on the relationship between aggressive media and behavior, especially in young children, is critical. Using a twin/triplets sample (N = 184 children), the authors investigated the association between preschoolers' preferred media choices and their aggressive behaviors. A multimeasure methodology was utilized, examining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…It would be interesting for further studies to expand our findings by taking into account multiple helping strategies. Finally, it is meritorious for future researchers to extend our findings by taking a broader perspective, and including more factors into consideration, especially given that there is no consistent evidence in the literature regarding the relations between violence exposure and violence-related attitudes and behaviors (e.g., Jamnik & Dilalla, 2018;Li et al, 2019;Mitrofan et al, 2014). For example, research has shown that personal characteristics (e.g., resilience, self-esteem), social resources (e.g., social support), and contextual factors (e.g., school setting) may moderate or buffer the effects of adversity (DeSmet et al, 2016;Li et al, 2019; Jiang et al…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…It would be interesting for further studies to expand our findings by taking into account multiple helping strategies. Finally, it is meritorious for future researchers to extend our findings by taking a broader perspective, and including more factors into consideration, especially given that there is no consistent evidence in the literature regarding the relations between violence exposure and violence-related attitudes and behaviors (e.g., Jamnik & Dilalla, 2018;Li et al, 2019;Mitrofan et al, 2014). For example, research has shown that personal characteristics (e.g., resilience, self-esteem), social resources (e.g., social support), and contextual factors (e.g., school setting) may moderate or buffer the effects of adversity (DeSmet et al, 2016;Li et al, 2019; Jiang et al…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…Another of the negative consequences of video games abuse is increased aggressiveness, a direct link having been identified between these two factors [ 13 , 14 ]. This is attributed to the violent nature of many video games, whose use is considered a risk factor for violent behavior [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This way, rGEs can be quantified. For example, the effect of exposure to aggressive media on aggressive behaviour in children may be partly explained by genetically driven media preferences [ 87 ]. Since multivariate models can also be applied to GWAS output [ 25 ], their scope and feasibility has increased.…”
Section: Onwards: Quantifying and Using Gene-environment Correlationsmentioning
confidence: 99%